The analysis of causes of cracks appearance on enamel coat at gray iron castings - Kovač, Risto (Journal of Production Engineering, 2023)
In this paper is given the analysis of causes of cracks appearance on enamel coat at gray iron casting, based on theoretical analysis of stress condition at gray iron casting and Practical observation during the enameling.